Pengaruh Efikasi Diri dan Keterampilan Digital Terhadap Kesiapan Kerja Menghadapi Era Society 5.0 Pada Mahasiswa Perbankan Syariah - Maulydia Anggraini; Hilda Hilda; Oki Sapitri Menghayati (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
Student work readiness is very important to face the dynamic world of work, students need to prepare for various challenges in the world of work, such as tight competition, high job demands, and rapid technological changes. This study aims to determine whether Self-Efficacy and Digital Skills partially and simultaneously affect Work Readiness to Face the Era of Society 5.0 in Islamic Banking Students of UIN Raden Fatah Palembang Class of 2021. The research method used is a quantitative approach. The sample in this study was 100 respondents with a sampling technique using random sampling with data measurement using a likert scale. Questionnaires were given to respondents and data analysis was carried out using SPSS 27 software. The results of this study indicate that partially the self-efficacy variable has an influence on the work readiness of islamic banking students with a significance value (sig) of 0.001 < (α) 0.1, and the digital skills variable has an influence on the work readiness of islamic banking students with a significance value (sig) of 0.002 < (α) 0.1. Meanwhile, simultaneously, self-efficacy and digital skills have a positive and significant influence on the work readiness of islamic banking students with a significance value (sig) of 0.000 < (α) 0.1.